Correlação entre os diagnósticos clínico, histopatológico e micológico de lesões bucais em portadores de próteses dentárias - Tavares, Gracielle Rodrigues (2009)
The objective of this study was to make a correlation between the clinical, mycologic and histopathological diagnosis of buccal lesions, in carrying patients of dental prostheses, in order to verify the degree of agreement between the same ones. 47 individuals were examined, of both the sorts, taken care of in the Service of Health of the Centro Odontológico de Cruz das Armas (COCA), in João Pessoa - PB, the period of January the August of 2009. The data were collected by means of intraoral clinical examination, being written down in a chart treatment the type of prostheses, hygiene form, frequency and time of use of the prostheses, type of lesion and description of the same one. After surgical removal of the lesions, the pieces were led to the histopathological analysis, in the Buccal Pathology Laboratory of the UFPB, to confirm the clinical diagnosis. All the patients were submitted to the mycologic examination, being the harvested samples of the palatal mucous and the surface of the prostheses, with swabs. After, they were carried to the Mycology Laboratory of the UFPB. When compared the clinical diagnosis with the histopathological diagnosis, it can be observed that it had a correlation between the results, but in 03 (16,8%) cases of HFI and 02 (40%) cases of HPI the histopathological diagnosis was not compatible with the clinical diagnosis. In the clinical diagnosis of prostheses-induced stomatitis it had rightness of 90,6% (23 cases) in the mycologic examination, while the negative clinical diagnosis the 73,3% (11 cases) rightness. It was concluded that the presence of other unrelated injuries to the use of prostheses (Oral squamaus papilloma, pyogenic granuloma) reflects a bigger attention of the surgeon-dentist as for the distinguishing diagnosis of these buccal lesions, requesting, whenever possible, the histopathological and mycologic examinations, for definitive diagnosis.